Hiperrealitas Kekuasaan Meta AI Dalam Dekonstruksi Cara Curhat Generasi Z di Era Digital Society 5.0 - Ida Bagus Suryanatha; Windi Susetyo Ningrum; Elia Damayanti; Muhamad Arief Rafsanjani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This study examines the shift in Generation Z’s confessional practices from interpersonal trust toward Meta AI as an effect of hyperreality and digital power structures, driven by trauma, privacy concerns, and experiences of social judgment. The research aims to decisively deconstruct how Meta AI shapes subjectivity, trust norms, and simulacral spaces in Gen Z disclosure practices. Using Critical Discourse Analysis informed by Baudrillard, Foucault, and Derrida, the study analyzes human–AI communications at textual, practice, and emotional-meaning levels. Findings show clearly that Meta AI reallocates trust from humans to machines, establishes a new regime of truth, manufactures hyperreal affective experiences, and fosters dependence on instant validation; concurrently it compresses opportunities for emotional negotiation and interpersonal repair. These dynamics normalize relational simulacra and erode collective empathy. The results point to the necessity of policy interventions and targeted digital-literacy programs to reconstitute spaces for authentic human dialogue and to mitigate the socio-emotional consequences of AI-mediated confessional cultures.